2016
DOI: 10.1101/095646
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Loss of the homologous recombination generad51leads to Fanconi anemia-like symptoms in zebrafish

Abstract: RAD51 is an indispensable homologous recombination protein, necessary for strand invasion and crossing over. It has recently been designated as a Fanconi anemia (FA) gene, following the discovery of two patients carrying dominant-negative mutations. FA is a hereditary DNA-repair disorder characterized by various congenital abnormalities, progressive bone marrow failure, and cancer predisposition. In this report, we describe a viable vertebrate model of RAD51 loss. Zebrafish rad51 loss-of-function mutants devel… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
5
0

Year Published

2018
2018
2020
2020

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(7 citation statements)
references
References 64 publications
2
5
0
Order By: Relevance
“…To fully understand functional annotations of genes in vivo, we screened the phenotypes of the mutants in embryogenesis, viability, growth, sex determination, hematopoiesis and sensitivity to DNA damaging agents. All the 33 homozygous mutants grew normally until 48 hpf with only four mutants showing morphological malformation and hematopoietic defects before 6 dpf, in line with observations that genomic homeostasis is linked to hematopoiesis (Farres et al 2015;Botthof et al 2017;Marsh et al 2018). Mutants of pcna and atad5a, two critical genes for DNA replication (Kang et al 2019a), showed reduced proliferation and induced apoptosis in the blood precursors at the CHT, while ddb1 and pcid2 homozygous mutants showed loss of HSPCs caused by reduced proliferation.…”
Section: Discussionsupporting
confidence: 80%
See 3 more Smart Citations
“…To fully understand functional annotations of genes in vivo, we screened the phenotypes of the mutants in embryogenesis, viability, growth, sex determination, hematopoiesis and sensitivity to DNA damaging agents. All the 33 homozygous mutants grew normally until 48 hpf with only four mutants showing morphological malformation and hematopoietic defects before 6 dpf, in line with observations that genomic homeostasis is linked to hematopoiesis (Farres et al 2015;Botthof et al 2017;Marsh et al 2018). Mutants of pcna and atad5a, two critical genes for DNA replication (Kang et al 2019a), showed reduced proliferation and induced apoptosis in the blood precursors at the CHT, while ddb1 and pcid2 homozygous mutants showed loss of HSPCs caused by reduced proliferation.…”
Section: Discussionsupporting
confidence: 80%
“…In addition, our six zebrafish mutants showed female-to-male sex reversal defects; blm -/-, brca2 -/-, fanci -/-, rad51 -/-, rad54l -/and rtel1 -/-. While rad54l -/and rtel1 -/mutants demonstrated a possible sex reversal phenotype with normal fertility like fanci -/homozygotes (Ramanagoudr-Bhojappa et al 2018), blm -/male animals were infertile without normal functional germ cells in the testis like brca2 -/and rad51 -/where primordial germ cells failed to survive and proliferate in the testes (Shive et al 2010;Botthof et al 2017). Although Blm homozygous KO mouse embryos were developmentally delayed and died by embryonic day 13.5 (Chester et al 1998), blm cu55/cu55 zebrafish survived and we were able to observe aberrant spermatogenesis, potentially recapitulating a phenotype of human male infertility in patients with Bloom syndrome (de Renty and Ellis 2017).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Deficiency of another critical member of this complex, rad51 , has recently been studied in zebrafish and shown to display symptoms of FA and smaller kidneys [78] . In light of this, other gene members of the FA pathway should be more closely scrutinized in the context of podocyte and kidney development to assess whether diminished DNA repair by other FA genes is causative of the fate switch seen between podocytes and IR in zep mutants.…”
Section: Discussionmentioning
confidence: 99%